A Pilot Trial of the Impact of Financial Incentive on the Utilization of Dental Services among Civil Servants in Ibadan, Nigeria (2019)
Financial constraints have been reported as major barriers to utilization of dental Services in developing countries. It is however unknown if financial incentives will improve dental Service utilization among civil servants in Nigeria. To evaluate the effect of financial incentive on the utilization of dental Services among civil servants in Ibadan, Nigeria. This was a pilot trial among two clusters of civil servants in Ibadan, Nigeria. In both groups, the civil servants participated in an oral health education programme, a dental screening exercise and referral for dental treatment. In addition to this, the experimental group got a financial incentive to present for treatment. The two groups were followed up for a period of twelve weeks. Data were analysed using SPSS. A total of 109 civil servants participated in the study. There were 62 in the control group and 47 in the experimental group. The mean age of the study participants in the control group was 42.1+8.75 years, mean DMFT was 0.95 + 1.87 and 94% of them had an unmet dental need. Similarly, in the experimental group the mean age was 44.7—11.68 years, mean DMFT was 0.45+0.95 and 98% of them had an unmet need. There was no significant difference between the two groups at baseline. At twelve weeks, none of those referred for treatment in the control group presented for treatment while only 3 (6.4%) experimental group presented for dental treatment. No statistical difference was observed (p=0.077). In this study financial incentive did not result in significant increased utilization of dental care Services among adults